Forecasting trachoma control and identifying transmission-hotspots - Blumberg, S; Prada, JM; Tedijanto, C; Deiner, MS; Godwin, WW; Emerson, PM; Hooper, PJ; Borlase, A; Hollingsworth, TD; Oldenburg, CE; Porco, TC; Arnold, BF; et al. (Oxford University Press, 2021)
Background: Tremendous progress towards elimination of trachoma as a public health problem has been made. However, there are areas where the clinical indicator of disease, trachomatous inflammation—follicular (TF), remains prevalent. We quantify the progress that has been made, and forecast how TF prevalence will evolve with current interventions. We also determine the probability that a district is a transmission-hotspot based on its TF prevalence (ie, reproduction number greater than one).